Comprehensive Study of Effective Microorganisms in Wastewater Treatment - Mohd Azmi, Nur Anis Ayuni; Saidon, Nur Zuhairah; Jamaludin, Nurul Natasya Nabila; Yahya, Izat (Multidisciplinary Applied Research and Innovation, 2025)
Effective Microorganisms (EM) are microbial cultures composed mostly of lactic acid bacteria, yeasts, and photosynthetic bacteria. Many of the microbes in these cultures are helpful to plants, people, animals, and the environment, and are utilized to create and increase the freshness of foods. This product has been widely used as a medium to improve water quality, mostly in rivers and lakes. This study focuses on the drainage area near Arked Mawar Cafeteria, UTHM Pagoh. The objectives of this study were to determine the raw data parameters values for Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), Ammoniacal Nitrogen (AN), initial pH, initial Dissolved Oxygen (DO), initial temperature and Suspended Solid (SS). Next is to determine the optimal parameter values for COD and BOD reduction using the Effective Microorganisms (EM). Lastly, to determine the optimal dose and time for COD and BOD reduction using Effective Microorganisms (EM). The primary goal of this study is to determine whether our product can treat wastewater from the UTHM cafeteria before releasing it into a lake or river. From a visual inspection test conducted, compared to before applying EM, the wastewater will gradually clear after adding EM. Results from a previous study show that EM is effective, lasting up to more than a month after application and having an average reduction effect of at least 45%. In this study, the reduction of Chemical Oxygen Demand (COD) and Biological Oxygen Demand (BOD) can all be achieved using an Effective Microorganisms (EM) treatment approach.